Effect of Working Memory on Students’ Attitude towards Mathematics at Secondary Level - Asim Nazir , Rizwan Akram Rana , Khateeb Ahmed Khan (PJE, 2023)
The aim of this study was to find out the influence of working memory on secondary school students’ attitude towards mathematics. The sample of the study was comprised of 1303 students of age 14-15. Digit backward test was used to measure the working memory capacity of the students whilequestionnaire was used for the measurement of their attitude towards mathematics. Data were analyzed using the chi-square test to find the effect of working memory capacity on students’ attitude towards mathematics at secondary level. Independent sample t-test was used to find the difference between students’ working memory capacity based on gender, grades, school type, residential area, and elective subjects. Results suggest that the working memory of the students is consistent with their age. Female students have higher working memory capacity than male students. Urban students have higher memory than rural students. Overall results revealed that students with higher working memory have better attitude towards mathematics than the students with low working memory capacity at secondary level.